Efektivitas Kebijakan Fiskal dan Moneter dalam Mendorong Pertumbuhan Ekonomi di Indonesia - S, Suripto (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Sustainable economic growth will have an impact on improving people's welfare. With high economic growth will reduce unemployment and ultimately improve people's lives. This research will examine the impact of fiscal policy and monetary policy in Indonesia on economic growth. "Which economic policy effectively affects economic growth". The data used are sourced from Bank Indonesia data from 1980 to 2015. The hypothesis proof will use the Davidson-MacKinnon J Test method. The results of the study show that policies to encourage economic growth are a mix of monetary and fiscal policy.